Temporal changes in pulmonary expression of key procoagulant molecules in rabbits with endotoxin-induced acute lung injury: elevated expression levels of protease-activated receptors - Jesmin, Subrina; Gando, Satoshi; Matsuda, Naoyuki; Sakuma, Ichiro; Kobayashi, Shigeaki; Sakuraya, Fumika; Hattori, Yuichi (Thrombosis and Haemostasis, 2004)
Recently a new concept has emerged implicating thrombin signaling as the “bridge” that connects tissue damage to hemostatic and inflammatory responses. In view of this concept, we hypothesized that induction of protease-activated receptor (PAR) expression may play a critical role in endotoxin-induced tissue injury through the cellular actions of thrombin. Thus, in this study, temporal changes in expression of key precoagulant molecules, including PARs, in lungs from rabbits rendered endotoxemic by 100 μg/kg lipopolysaccharide (LPS) were examined with measurements of variables reflecting acute lung injury (ALI). ALI induction by LPS was confirmed by blood gas derangement, lung vascular hyperpermeability, and histopathological changes, and was characterized by the deposition of fibrin in the alveolar spaces, bronchioles and vessels. Plasminogen activator inhibitor-1 (PAI-1) and tissue factor (TF) were highly expressed in lungs after LPS injection. While the peaks in levels of PAI-1 and TF were comparable (12∼13-fold from control), their expression time-courses were different: PAI-1 exhibited a bell-shaped expression pattern and peak at 6 h, whereas TF level reached maximum at 10 h. Of note, LPS induced a rapid and significant increase in levels of PAR-1 compared to control, with a peak level at 1 h (3.3-fold). Although declining thereafter, it remained significantly higher than the control level throughout the study period. Expressions of PAR-2, -3, and -4 were also increased by LPS with different time courses from PAR-1 expression. Immunofluorescence staining for PAR-1 were localized in blood vessels, bronchial epithelium, and alveolar pneumocytes after LPS. These results suggest that the increased expression levels of PARs, in addition to PAI-1 and TF, may, in part, underlie the development of ALI occurring during endotoxemia.
Keywords: Acute lung injury; endotoxin; fibrin deposition; plasminogen activator inhibitor-1; protease-activated receptors; tissue factor; tumor necrosis factor-α